2021
DOI: 10.30867/gikes.v2i1.429
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas kimia dan organoleptik nugget ikan gabus melalui penambahan tepung kacang merah

Abstract: Background: The addition of red bean flour is an alternative to increase protein content. Red bean nuggets also still have low protein content, it is necessary to add protein from animal sources. One of the high protein fish is snakehead fish which reaches 25.1% while 6.224% of the protein is in the form of albumin in synergy with the mineral Zn.Objective: The research objective was to measure the effect of adding red bean flour to the organoleptic test (color, texture, aroma, taste) of snakehead fish nuggets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
0
0
2
Order By: Relevance
“…Carrot flour is high in fiber and low in calories, thus it can improve the nutritional value of food products. Similar research conducted by Yulianti et al (2018), Anggraini et al (2021), andAyu et al (2022), it also showed that the addition of carrot flour to fish nuggets can increase the protein and fiber content of the product, as well as increase the liking level of consumers towards the product.…”
Section: Introductionsupporting
confidence: 78%
“…Carrot flour is high in fiber and low in calories, thus it can improve the nutritional value of food products. Similar research conducted by Yulianti et al (2018), Anggraini et al (2021), andAyu et al (2022), it also showed that the addition of carrot flour to fish nuggets can increase the protein and fiber content of the product, as well as increase the liking level of consumers towards the product.…”
Section: Introductionsupporting
confidence: 78%
“…Merisna et al, (2016) menjelaskan bahwa fungsi bahan pengikat adalah memperbaiki stabilitas emulsi, menurunkan penyusutan akibat pemasakan, memberikan warna yang terang, meningkatkan elastisitas produk, membentuk tekstur yang padat dan menarik air dalam adonan. Bahan pengikat yang biasanay digunakan untuk menyatukan adonan antara lain tepung tapioka, tepung beras, tepung maizena, tepung sagu dan tepung terigu (Andriani et al, 2023;Anggraini & Andriani, 2021).…”
Section: Hasil Dan Pembahasanunclassified
“…Kebanyakan masyarakat mengkonsumsi ikan air laut dibanding air tawar meskipun ikan air tawar juga memiliki nilai gizi yang cukup tinggi. Pengolahan ikan sudah banyak dilakukan dengan menjadikan produk yang mempunyai daya simpan yang lama salah satunya abon ikan (Anggraini & Andriani, 2020).…”
Section: Pendahuluanunclassified